Usefulness of fetal magnetic resonance imaging for postnatal management of congenital lung cysts: prediction of probability for emergency surgery - Chiyoe Shirota; Takahisa Tainaka; Toshiki Nakane; Yujiro Tanaka; Akinari Hinoki; Wataru Sumida; Naruhiko Murase; Kazuo Oshima; Kosuke Chiba; Ryo Shirotsuki; Hiroo Uchida (BMC, 2018)
Abstract Background Emergency rescue lung resection is rarely performed to treat congenital lung cysts (CLCs) in neonates. Many reports have described fetal CLC treatment; however, prenatal predictors for postnatal respiratory failure have not been characterized. We hypothesized that fetal imaging findings are useful predictors of emergency surgery. Methods We retrospectively studied patients with CLC who underwent lung surgery during the neonatal period in our hospital between January 2001 and December 2015. The demographic data, fetal imaging findings, and intra- and postoperative courses of patients who underwent emergency surgery (Em group) were compared with those of patients who received elective surgery, i.e., non-emergency surgery (Ne group). Results The Em group and Ne group included 7 and 11 patients, respectively. No significant difference was noted in gestational age, time at prenatal diagnosis, birth weight, and body weight at surgery. The volumes of contralateral lung per thoracic volume were significantly smaller in the Em group than in the Ne group (p = 0.0188). Mediastinal compression was more common in the Em group (7/7) than in the Ne group (4/11) (p = 0.0128). Conclusions This is the report describing neonatal emergency lobectomy in patients with CLC evaluated by fetal MRI using the lung volume ratio and mediastinal shift. In patients with CLC, mediastinal shift and significant decreases in contralateral lung volumes during the fetal stages are good prenatal predictors of postnatal emergency lung resection.